Determination of Hg(II) with square-wave anodic stripping voltammetry method on AuNPS/ErGO-GCE electrode - Hà, Thuỳ Trang; Hoàng, Hồ Thùy Dương; Huỳnh, Văn Chung; Nguyễn, Đình Luyện; Nguyễn, Hải Phong (Hue University Journal of Science: Natural Science, 2025)
In this study, Hg(II) was determined on a modified AuNPs/ErGO-GCE electrode with the square-wave anodic stripping voltammetry (SqW-ASV) method. The morphology of the material modifying the electrode was characterized with EDX-mapping and HR-TEM. Additionally, several parameters of the SqW-ASV method, including pulse amplitude (ΔE), square wave frequency (f), potential change step (r), deposition potential (Edep.), and deposition time (tdep.), were investigated. Under optimized conditions: acetate buffer (ABS), pH = 5 and KCl 0.1 M, r from –0.2 to +0.8 V, Edep: –0.9 V, tdep: 240 s, DE: 30 mV and f: 30 Hz, the linear range of Hg(II) concentration was from 5.0 to 49,5 ppb, and the detection limit of Hg(II) was 1.89 ppb.